Pengaruh Desentralisasi Fiskal dan SILPA terhadap Belanja Modal Pemerintah Kab/Kota di Sumatera Selatan - Mila Amelia; Periansya Periansya (Universitas Batanghari, 2022)
This study aims to determine the effect of Fiscal Decentralization and SILPA either partially or simultaneously on Capital Expenditures. This type of research is quantitative research. The sample used as many as 17 districts / cities in the province of South Sumatra. The type of data used is documentation so that the data obtained is secondary data. The data analysis method used multiple linear regression analysis. The results of this study indicate that (1) Fiscal Decentralization has a positive and significant effect on Capital Expenditures (2) SILPA has a positive and significant effect on Capital Expenditures (3) Fiscal Decentralization and SILPA simultaneously have a positive and significant effect on Capital Expenditures. The result of the determination test is known that R2 is 26%. These results can be concluded that Capital Expenditure is influenced by Fiscal Decentralization and SILPA by 26%, while the remaining 74% is influenced by other factors not examined in this study.